Development of a speed warning device for micro-mobility devices II - Abhishek Veer Shetty (Nanyang Technological University, 2023)
Micro Mobility Devices in Singapore has seen spike in the usage of Power Assisted Bicycles (PAB) and bicycles due to the change in Personal Mobility Devices (PMD), laws since 3rd Apr 2020 [1], which restricts their uses greatly. Additionally, there has also been more pressure to switch to the cheaper modes of transport such as PABs and bicycles over the use of motorcycles or cars due to the surges in COE prices of these vehicles, more than doubling in prices in over a year [2]. To make matters worse, the ongoing Russian conflict with Ukraine has caused fuel prices to spike. For e.g., the price of 95-octane grade petroleum has seen almost a $0.30 dollar increase in a week following the war [3]. All these have contributed to the increase in the number of riders, both bicycles and PABs. Not surprisingly, this has also led to more incidents and accidents on the roads involving bicycles and PABs. Hence, this project aims to upgrade a warning device for these mobility devices, from past versions from the seniors, to a more robust one with better functionality.